FREQUENCY AND FACTORS EFFECTING NON CLEARANCE OF LOWER POLE RENAL STONES - Ullah, Amin; Zubair, Mohammad; Khan, Nouman; Malik, Asif (Journal of Ayub Medical College Abbottabad, 2015)
Background: Renal stone disease is a major health hazard in Pakistan and extra-corporeal shockwave lithotripsy is one of comprehensive method used to treat these stones. The aim of this study is to determine the frequency of factors affecting the non-clearance of stone fragments of lower pole renal stone after extra corporeal shockwave lithotripsy. The study was done with the objective to determine the frequency the spatial anatomical factors which can influence the non-clearance of lower pole stone fragments after ESWL. Methods: One and nineteen (119) patients with lower pole renal stone less than10mm were subjected to maximum 3 sessions of extracorporeal shock wave lithotripsy. KUB radiographs, ultrasonography and intravenous urography were used as investigative tools for lower pole renal calyceal anatomy. X ray KUB and ultrasound were done after a week for clearance. Data was analysed with the help of SPSS version 10.0 and presented in the forms of tables and graphs. Results: There were 77 (64.71%) males and 42 (35.29%) females. Infundibulo-pelvic angle (IPA)>40º was present in 93 (78.15%), Infundibular length (IL) <22 mm in 107 (89.92%) and Infundibular width (IW) >4 mm was present in 100 (84.03%) patients. The frequency of stone non clearance was noted in 31 (26.05%). Infundibulo-pelvic angle (IPA)>40º (p=0.000), Infundibular length (IL)<22 mm (p=0.001) and Infundibular width (IW)>4 mm (p=0.046) were significant variables affecting stone clearance. Conclusion: The frequency of non-clearance of lower calyx of kidney stone is 26.05%. The clearance of fragments of the lower calyx kidney stones is affected by three spatial anatomical factors, i.e., Infundibulopelvic angle, Infundibular width and infundibular length. Keywords: Extracorporeal shock wave lithotripsy; non clearance of lower pole kidney stones; Infundibulopelvic angle; Infundibular width; infundibular length.